2012
DOI: 10.1186/1471-2393-12-85
|View full text |Cite
|
Sign up to set email alerts
|

‘Groping through the fog’: a metasynthesis of women's experiences on VBAC (Vaginal birth after Caesarean section)

Abstract: BackgroundVaginal birth after Caesarean section (VBAC) is a relevant question for a large number of women due to the internationally rising Caesarean section (CS) rate. There is a great deal of research based on quantitative studies but few qualitative studies about women's experiences.MethodA metasynthesis based on the interpretative meta ethnography method was conducted. The inclusion criterion was peer-review qualitative articles from different disciplines about women's experiences of VBAC. Eleven articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 27 publications
2
96
2
2
Order By: Relevance
“…Clinicians spoke about the value of evidence in making decisions about the mode of birth, but were very clear that they took into account many other factors in their decision-making process. Studies have found that significant variations in the rates of attempted VBAC [24] suggest that the decision-making process around the birth mode after a previous CS is complicated and multidimensional for both women and care providers, and this certainly was the case for the clinicians in this study. According to a meta-synthesis of the views of women, they need evidence-based information on both the risks and the positive aspects of VBAC [25].…”
Section: Discussionmentioning
confidence: 87%
“…Clinicians spoke about the value of evidence in making decisions about the mode of birth, but were very clear that they took into account many other factors in their decision-making process. Studies have found that significant variations in the rates of attempted VBAC [24] suggest that the decision-making process around the birth mode after a previous CS is complicated and multidimensional for both women and care providers, and this certainly was the case for the clinicians in this study. According to a meta-synthesis of the views of women, they need evidence-based information on both the risks and the positive aspects of VBAC [25].…”
Section: Discussionmentioning
confidence: 87%
“…We do not know how many women currently have the opportunity to consider or discuss planning a vaginal birth following a prior CS, nor do we know why women in our study opted for a home birth. Studies of women's decision‐making about mode of birth in a subsequent pregnancy after CS show that this can be complex and conflicted, particularly with regard to balancing safety with women's expressed ‘need’ to experience labour and ‘normal birth’ . These studies also demonstrate the importance of information from health professionals in women's decision‐making; in one study, women reflected that this information could be unclear and contradictory and in another that they experienced ‘latent communication’ from health professionals who simultaneously presented ‘official’ messages of choice while revealing personal views which gave women the impression that their choices would be restricted .…”
Section: Discussionmentioning
confidence: 99%
“…Third, some women have an overwhelming desire to experience labour and vaginal birth, seeing it as fundamental to their perception of femininity and motherhood. Many feel that the initial mother–baby bond is stronger with a vaginal birth compared with caesarean section …”
Section: Factors Influencing Women's Decisions On Vbacmentioning
confidence: 99%